THE DYNAMICS OF CREATIVITY: MAPPING OPPURTUNITIES AND CHALLENGES IN THE CREATIVE ECONOMY OF LHOKSEUMAWE - Mutia Rahmah; Noviami Trisniarti; Muhammad Hafizh; Ratih Widyadhana; Rezeki Fitri Tritami (CV. Radja Publika, 2024)
This study aims to analyze the opportunities and challenges in the development of the creative economy in Lhokseumawe City using a SWOT-based approach. A descriptive qualitative method was applied, with data collected through in-depth interviews, observations, and documentation involving key stakeholders, including creative industry actors, government representatives, academics, and communities. The data were analyzed using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices to identify internal and external strategic factors. The results indicate that the IFAS score is 2.40 and the EFAS score is 2.40, reflecting moderate internal and external conditions. The strength score (1.50) and opportunity score (1.50) indicate that the sector is supported by strong internal potential and favorable external conditions. Based on the Cartesian SWOT analysis, the creative economy in Lhokseumawe City is positioned in Quadrant I, suggesting the implementation of an aggressive strategy. Therefore, optimizing strengths and opportunities through innovation, digital transformation, and stakeholder collaboration is essential to support sustainable development.